Signaling Mediated by Toll-Like Receptor 5 Sensing of Pseudomonas aeruginosa Flagellin Influences IL-1β and IL-18 Production by Primary Fibroblasts Derived from the Human Cornea - Cendra, Maria del Mar; Christodoulides, Myron; Hossain, Parwez (Frontiers in Cellular and Infection Microbiology, 2017)
Pseudomonas aeruginosa is the principal cause of bacterial keratitis worldwide and overstimulation of the innate immune system by this organism is believed to contribute significantly to sight loss. In the current study, we have used primary human corneal fibroblast (hCF) cells as an ex vivo model of corneal infection to examine the role of P. aeruginosa flagellum and type three secretion system (TTSS) in inducing inflammasome-associated molecules that trigger IL-1β and IL-18 production during the early stages of the infection. Our results show that P. aeruginosa infection stimulated the non-canonical pathway for IL-1β and IL-18 expression and pathway stimulation was influenced predominantly by the flagellum. Both IL-1β and IL-18 cytokines were expressed intracellularly during bacterial infection, but only the former was released and detected in the extracellular environment. We also investigated the signaling pathways in hCFs mediated by Toll-Like Receptor (TLR)4 and TLR5 sensing of P. aeruginosa, and our data show that the signal triggered by TLR5-flagellin sensing significantly contributed to IL-1β and IL-18 cytokine production in our model. Our study suggests that IL-18 expression is wholly dependent on extracellular flagellin sensing by TLR5, whereas IL-1β expression is also influenced by P. aeruginosa lipopolysacharide. Additionally, we demonstrate that IL-1β and IL-18 production by hCFs can be triggered by both MyD88-dependent and -independent pathways. Overall, our study provides a rationale for the development of targeted therapies, by proposing an inhibition of flagellin-PRR-signaling interactions, in order to ameliorate the inflammatory response characteristic of P. aeruginosa keratitis.